Optimizing Educational Processes: Strategies for Enhanced Primary and Secondary Education Implementation - Farida Farida; Dewi Ningsih; Agus Pahrudin (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
The research aims to describe the implementation of primary and secondary education in schools. The type of research used in this research is descriptive qualitative. The subjects of this research were school principals, teachers, and students—data collection techniques through observation, interviews, documentation, questionnaires, and triangulation (combination). Data analysis techniques are carried out by reducing data, compiling data presentation, drawing conclusions, and verification. The research findings are that strategies for improving the implementation of primary and secondary education in optimizing the educational process can be implemented by schools and madrasas by planning the implementation of education, expansion and equalization of opportunities for quality basic education, including the development of alternative education; developing curriculum according to the needs of educational institutions (modifying); preparing school activity plans and budgets, managing according to technical instructions, making accountability letter and financial reports. The need for improvements in several crucial aspects of the education system, namely the development of a more relevant and effective curriculum, strategies for managing education funds that can optimize the use of available financial resources, effective education expansion, and equity strategies, increasing the competence of teachers and teaching staff are also important implications. This research stimulates innovation in the education system, such as the development of new learning methods or the integration of technology in the learning process, with concrete steps that educational institutions and policymakers can take to improve the quality and access to primary and secondary education, ensuring that all individuals have an equal opportunity to receive a quality education.